Moving health sovereignty in Africa disease, governance, climate change (Routledge, 2016)
Today's era of intense globalization has unleashed dynamic movements of people, pathogens, and pests that overwhelm the static territorial jurisdictions on which the governance provided by sovereign states and their formal intergovernmental institutions is based.